Men's access to outpatient psychosocial cancer counseling - Singer, Susanne; Wunsch, Alexander; Ihrig, Andreas; Bruns, Gudrun; Holz, Franziska; Jakob, Johannes; Besseler, Markus; Engesser, Deborah; Blettner, Maria; Koenig, Jochem; Bayer, Oliver (Deutsches Ärzteblatt, 2024)
Background: Men make use of outpatient cancer counseling less commonly than women, even when they stand to benefit from it. Method: In a cluster -randomized trial (registered under DRKS00032181), we studied whether measures on multiple levels (information for referring physicians, public information, structural changes, offerings specifically for male patients) over a period of 12 months would be able to increase the percentage of men among patients seeking outpatient cancer counseling (primary endpoint, initial contact; secondary endpoint, all contacts). The intervention effect was quantified by the fitting of generalized linear mixed models to obtain an odds ratio, which was adjusted for cluster structure and for the percentages of first contacts and of all contacts during the 12 months before the start of the intervention. Results: In 12 regions of Germany (6 each in the intervention arm and the control arm), 11 986 people had first contacts with outpatient cancer counseling, 6004 of them during the intervention phase. The percentage accounted for by men was 30.7% in the intervention arm and 25.7% in the control arm, corresponding to a statistically insignificant model -based adjusted odds ratio (OR) of 1.2 (95% confidence interval [1.0; 1.4], p = 0.08) for the primary endpoint. There were a total of 51 842 counseling sessions (both initial contacts and subsequent contacts), 26 651 of them in the intervention phase. The percentage of these that was accounted for by men was 27.6% in the intervention arm and 22.2% in the control arm; the adjusted OR for this secondary endpoint was 1.3 [1.1; 1.6], p = 0.01). Conclusion: The targeted implementation of malespecific measures on multiple levels can increase, by a small amount, the percentage of men among persons seeking outpatient cancer counseling.